2022
DOI: 10.3390/cells11040731
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Paternal Age Effects and Sperm Methylation Levels of Developmentally Important Genes

Abstract: A growing number of sperm methylome analyses have identified genomic loci that are susceptible to paternal age effects in a variety of mammalian species, including human, bovine, and mouse. However, there is little overlap between different data sets. Here, we studied whether or not paternal age effects on the sperm epigenome have been conserved in mammalian evolution and compared methylation patterns of orthologous regulatory regions (mainly gene promoters) containing both conserved and non-conserved CpG site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…A similar correlation was found in the pig longissimus dorsi muscle, where a global loss of DNA methylation in the gene body region in skeletal muscle of middle-aged pigs was found compared with the young group [ 22 ]. Similar to this study, species-specific or breed-specific DNA methylation patterns were also observed when comparing human, bovine, and mouse DNA methylation patterns [ 23 ]. In this study, we found that gene expression and DNA methylation were negatively correlated only in regulatory regions around TSSs.…”
Section: Discussionsupporting
confidence: 79%
“…A similar correlation was found in the pig longissimus dorsi muscle, where a global loss of DNA methylation in the gene body region in skeletal muscle of middle-aged pigs was found compared with the young group [ 22 ]. Similar to this study, species-specific or breed-specific DNA methylation patterns were also observed when comparing human, bovine, and mouse DNA methylation patterns [ 23 ]. In this study, we found that gene expression and DNA methylation were negatively correlated only in regulatory regions around TSSs.…”
Section: Discussionsupporting
confidence: 79%
“…In a candidate gene study [ 39 ], we identified three sperm ageDMRs in humans, four in bovine, and three in mice, which were all species-specific. Here, we show a species-specific effect of paternal age on HSA19, which has not been conserved in the marmoset.…”
Section: Discussionmentioning
confidence: 99%
“…Breed-specific HMRs of three commercial pig breeds are also reported to be related to phenotypic changes [ 49 ]. Interestingly, age-related differentially methylated regions (ageDMRs) were reported to be largely species-specific based on bisulfite pyrosequencing data from 10 regions [ 50 ]. The authors stipulated that ageDMRs in the epigenomic evolution regions may explain the lineage-specific environmental adaptations and predict the age-dependent sperm-related traits.…”
Section: The Epigenome Of Bovine Spermmentioning
confidence: 99%